Cigarette smoke extract and heated tobacco products promote ferritin cleavage and iron accumulation in human corneal epithelial cells - Wataru Otsu (Nature Portfolio, 2021)
Abstract The cornea is directly exposed to cigarette smoke, and smoking is a risk factor for several corneal diseases including dry eye syndrome. Currently, heated tobacco products (HTPs) are widely used as substitutes for cigarette smoking around the world. In the present study, we investigated the molecular mechanism(s) leading to cellular injury induced by cigarette smoke extract (CSE) or HTPs. Exposure to CSE perturbed the formation of tight junctions, leading to an increase in cell volume, a decrease in transepithelial electrical resistance (TER) in the human corneal epithelial cell-transformed (HCE-T) cell line. Moreover, CSE exposure induced both lipid peroxidation and ferrous [Fe(II)] ion accumulation in autolysosomal compartments. Interestingly, a cleaved form of ferritin appeared when HCE-T cells were incubated with CSE. This aberrant ferritin processing was suppressed by treatment with autophagy inhibitors. Furthermore, the CSE-induced cell death was suppressed by either ferrostatin-1 or deferoxamine (DFO). CSE exposure also promoted the expression of cytokines whereas DFO treatment inhibited the CSE-induced expression of these cytokines. Exposure to HTPs also induced both HCE-T cell death and cleaved ferritin accumulation in a concentration- and time-dependent manner. These results indicated that CSE or HTPs activated the ferroptosis signaling pathway, which contributed to corneal epithelial cell injury.